Soil seed banks in the floodplain of a large river: A test of hypotheses on seed bank composition in relation to flooding and established vegetation. (27th June 2019) - Greulich, Sabine; Chevalier, Richard; Villar, Marc
Abstract: Questions: This study investigates soil seed banks in relation to established vegetation in the floodplain of a large river with high‐energy floods. It addresses the composition of seed banks and extant vegetation over a wide flooding and succession gradient. Tested hypotheses were: (a) species richness and seed bank density are highest in mid‐succession habitats; (b) seed bank variability increases with succession; (c) the proportion of species in the established vegetation with permanent seed banks declines with succession; and (d) similarity between vegetation and seed bank declines with succession. Location: Mareau‐aux‐Prés, the Loire River, close to Orléans, France. Methods: Seed banks and vegetation were sampled in five habitats from a succession series: (a) Pioneer vegetation of shores and sandbanks; (b) softwood shrubs; (c) softwood forest; (d) mature forest; and (e) Elytrigia ‐dominated grasslands. Sample units were 5 m × 5 m plots. Soil samples were taken from the upper 6 cm. Seed banks were studied via the seedling emergence method, followed by screening of sediment for remaining seeds. Composition of seed banks was compared to that of vegetation using the Sørenson similarity index. Results: Seed bank density varied between 260 and 11, 260 seeds/m 2 . Clear differences between habitats existed in the composition of species in seed banks and established vegetation. Seeds of most dominant species were distributed across the whole range of floodplain habitats but species were more restricted in the vegetation. Species richness and seed bank densities did not vary with succession as expected, but the proportion of species that produce persistent seed banks did decline with succession. Conclusions: Floodplains of large rivers provide an excellent context to test hypotheses about the processes that influence the links between seed banks and standing vegetation. In the case of high‐energy floods and high sediment dynamics, the methods commonly used to study seed banks can, however, be questioned. Abstract : We investigated characteristics of seed banks and standing vegetation across the dynamic floodplain of a large river. Five major habitat types were taken into account, covering the entire succession gradient, from pioneer habitats to major forest. The study tested a series of hypothesis on seed banks and vegetation across disturbance gradients and analyzed species composition and distribution patterns.